(3CSFdI hCLhHI aj GdWHs
(3ChdgG (B:s
(3eHJhQ , hChd GdehLhO efgG (B: (3GdUaQGA hGdeQI GdShOGA eGbhI GdOe ? MGQ WH HGYJOGd eG bhI GdHdZe ? HGOQ WH s
(3BNQgG (B:s
(3aeKd eG jOd bQMI Jchf ai GdeKGfI Ch ai GdcdjJjf Ch ai GdbVjH ef GdQLd Ch ai GdaQL ef GdeQCI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B86 - (3U(B163s
(3GfXQgG eY JdNjU cJGH GdMejGJ Qbe (B" 423"s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B19 s
Keywords: (3GdWHs